A review of a phenomenological model for magnetocaloric effect in ferromagnetic materials. (1st February 2017) - Zouari, R.; Chehaidar, A.
ABSTRACT: The present work is devoted to a review of the phenomenological model proposed by Mahmoud Aly Hamad (M. Aly Hamad, Phase Transitions 85 (2012) 106–112) to predict the magnetocaloric effect in ferromagnetic material from the only measure of its magnetization as a function of temperature under an applied magnetic field. We questioned the reliability of that model. Based on some experimental data available in the literature, we have shown that, contrary to what is expected, the prediction of the magnetocaloric effect by this model is poor.